Models for Simulation of Travelling-Wave Deflection Systems - Staras, S. (Elektronika ir Elektrotechnika, 2000)
Models for simulation of electron beam deflection and calculation of dynamic characteristics of oscillographic travelling–wave cathode-ray tubes and travelling-wave deflection systems are developed. Simulation allows to determine influence of various factors on tube characteristics in time and frequency domains and formulate the requirements for characteristics of traveling-wave deflection systems. Software for calculation of dynamic characteristics of helical and meander travelling wave deflection systems, travelling-wave cathode ray tubes and vertical deflection channels was developed using the models. Simulation of the systems and channels are widely used in design and search for optimal decisions and allows to shorten the design process of deflecting systems and travelling-wave cathode-ray tubes.